A dual timescale active power coordinated scheduling framework for wind integrated power system in the presence of storage and wind forecast uncertainties. (13th April 2016) - Jiang, Ping; Huo, Yuchong; Wu, Xi
Summary: This paper proposes a dual timescale active power coordinated scheduling framework to accommodate large scale wind power integration. This framework is composed of rolling scheduling, real‐time scheduling and storage control. The optimization model of rolling scheduling policy is presented, which is activated every 30 min using the renewed forecast to modify the day‐ahead scheduling curve. Also the optimization model of real‐time scheduling is put forward, which is triggered every 15 min using the renewed forecast to modify the output of balance generators. In addition, the optimal storage control strategy is presented. The efficiency of the dual timescale active power coordinated scheduling framework is verified via the IEEE RTS bus system. Copyright © 2016 John Wiley & Sons, Ltd.